(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare the effectiveness of iron sucrose and ferric carboxymaltose in treating iron deficiency among patients suffering from chronic kidney disease who were undergoing maintenance hemodialysis. Methods: In this comparative study, we included 100 patients with chronic kidney disease (CKD) on maintenance hemodialysis for more than 6 months. The patients were recruited from September 2024 to February 2025. The patients receiving ferric carboxymaltose (FCM) therapy (group A) were administered a single intravenous infusion ranging from 10 to 15 mg/kg, not exceeding a total of 1000 mg. In group B, intravenous IS was given in a total dose of 1000 mg in 14 days, a 200 mg undiluted injection over five minutes was given after every alternate day. Mean increase in Hb and ferritin levels from baseline value were the primary study outcomes. Hb and ferritin levels were measured after 4 weeks of treatment and then after 3 months to determine mean increase. Results: The average age of individuals in the FCM group was 57.5 years (±7.8), while those in the IS group had a slightly higher average age of 58.3 years (±8.1). At baseline, hemoglobin levels were similar between the groups. After four weeks, Group FCM exhibited an increase in hemoglobin to 9.9±1.2 g/dL, while Group IS reached 9.4±1.3 g/dL (p-value 0.04). By the three-month mark, Group FCM significantly improved their hemoglobin levels to 11.1±1.4 g/dL compared to Group IS at 9.9±1.2 g/dL (p-value <0.0001). y three months, Group FCM recorded an impressive serum ferritin level of 84.8±17.4 mg/L, while Group IS only reached 27.4±5.3 mg/L (p-value <0.0001). Conclusion: In hemodialysis patients, intravenous ferric carboxymaltose (FCM) is more effective than intravenous iron sucrose (IS) in treating iron deficiency anemia. This research supports the use of FCM as an innovative option for treating IDA. It provides patients with a highly effective iron supplement that is also characterized by a favorable safety record.